2011
DOI: 10.2903/j.efsa.2011.2393
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on risk based control of biogenic amine formation in fermented foods

Abstract: A qualitative risk assessment of biogenic amines (BA) in fermented foods was conducted, using data from the scientific literature, as well as from European Union‐related surveys, reports and consumption data. Histamine and tyramine are considered as the most toxic and food safety relevant, and fermented foods are of particular BA concern due to associated intensive microbial activity and potential for BA formation. Based on mean content in foods and consumer exposure data, fermented food categories were ranked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
276
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 677 publications
(322 citation statements)
references
References 228 publications
(280 reference statements)
4
276
2
Order By: Relevance
“…Standarová et al (2010) described that Olomouc tvorogs also contained, among other amines, the highest level of cadaverine, up to 2413 mg kg −1 . According to European Food Safety Authority (2011), fresh cheeses can contain from 10.7 to 45 mg kg −1 of cadaverine and the hard cheeses from 47.8 to 83.5 mg kg −1 ; but in some kinds of hard cheeses, the amine level can reach as much as 3170 mg kg −1 . Research of Sawilska-Rautenstrauch et al (2010) showed that cadaverine content in camembert is lower than 2.6 mg kg −1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Standarová et al (2010) described that Olomouc tvorogs also contained, among other amines, the highest level of cadaverine, up to 2413 mg kg −1 . According to European Food Safety Authority (2011), fresh cheeses can contain from 10.7 to 45 mg kg −1 of cadaverine and the hard cheeses from 47.8 to 83.5 mg kg −1 ; but in some kinds of hard cheeses, the amine level can reach as much as 3170 mg kg −1 . Research of Sawilska-Rautenstrauch et al (2010) showed that cadaverine content in camembert is lower than 2.6 mg kg −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Much higher level of this amine was stated by Standarová et al (2010) in Olomouc cheeses (1058 mg kg −1 ) and by Fiechter et al (2013) in harzer cheese (516 mg kg −1 ). European Food Safety Authority (2011) reported that this amine content can reach, in fresh cheeses 48 mg kg −1 , in hard cheeses 65.5 mg kg −1 , and in acid-curd cheeses 55.3 mg kg −1 ; although much higher amounts were observed in some cheeses—in cheddar 910 mg kg −1 and 140 mg kg −1 in camembert.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations